2015
DOI: 10.1371/journal.pone.0134310
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Circulating MiRNA in Bovine Serum and Their Potential as Novel Biomarkers of Early Mycobacterium avium subsp paratuberculosis Infection

Abstract: Mycobacterium avium subspecies paratuberculosis (MAP) is the aetiological agent of Johne’s disease (JD), a chronic enteritis in ruminants that causes substantial economic loses to agriculture worldwide. Current diagnostic assays are hampered by low sensitivity and specificity that seriously complicate disease control; a new generation of diagnostic and prognostic assays are therefore urgently needed. Circulating microRNAs (miRNAs) have been shown to have significant potential as novel biomarkers for a range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 67 publications
4
59
2
Order By: Relevance
“…Despite extensive evidence in humans, the potential utility of circulating miRNAs as tissue biomarkers in livestock has not been explored widely, with a handful of recent studies identifying potential biomarkers of metabolic status and infection in chicken, pig and cow [2022]. We recently reported for the first time changes in circulating miRNA levels during early pregnancy (Days 16 and 24) in cattle [23].…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive evidence in humans, the potential utility of circulating miRNAs as tissue biomarkers in livestock has not been explored widely, with a handful of recent studies identifying potential biomarkers of metabolic status and infection in chicken, pig and cow [2022]. We recently reported for the first time changes in circulating miRNA levels during early pregnancy (Days 16 and 24) in cattle [23].…”
Section: Introductionmentioning
confidence: 99%
“…Quantifying miRNA abundance in serum from cattle stratified based on JD presentation (control, mild, moderate, severe) they revealed that a model employing the expression of just 4 miRNA could separate moderate and severely infected animals from the control and mild animals. Conversely, in our previous work using samples from experimental MAP infection models, no significant differential abundance in circulating miRNA could be detected using RNA-seq when comparing uninfected to early stage MAP infection 11 , or from early vs late stage MAP infection 12 .…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies in MAP infected cattle have measured miRNA expression in serum 8 , whole blood 9 and ileal tissues 10 . We have previously investigated circulating miRNA expression in peripheral blood at silent and subclinical MAP infection stages but detected minimal changes that did not provide diagnostic benefit 11,12 . It may, however, be more rewarding to investigate extracellular miRNAs at a local level, with faeces providing a route to explore miRNA species and abundance in the context of the intestinal immune response.…”
Section: Extracellular Micrornas (Mirnas) Are Detectable In the Peripmentioning
confidence: 99%
“…Recent studies on profiling of miRNAs during clinical and subclinical infection of MAP gave a new perspective to MAP control via miRNA techniques. These studies shown that circulating miRNAs in MAP infected animals retain their integrity under longterm suboptimal storage temperatures and are considered as potential biomarkers [164, 165] that can be exploited for devising the future paratuberculosis control strategies. Apart from miRNAs several compounds such as AS101, SD169 and niclosamide can be used to target IL-10 mediated anti-inflammatory activity.…”
Section: Resultsmentioning
confidence: 99%